Tinjauan Yuridis terhadap Perlindungan Hukum bagi Pengawas Pemilu Tahun 2024 di Kabupaten Bone Bolango - Najwa Nur'ain Hadju; Zamroni Abdussamad; Janwar Hippy (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
This study analyzes the form and implementation of legal protection for election supervisors in the 2024 General Election in Bone Bolango Regency and formulates an ideal model for future protection. It adopts a normative legal approach supported by empirical data, using statutory and conceptual methods. The findings indicate that existing protection is inadequate due to a normative gap in Law No. 7 of 2017, which does not explicitly regulate the occupational safety of supervisors. Furthermore, Article 491 remains repressive and limited to the campaign stage. In practice, supervisors experience psychological pressure and intimidation without effective advocacy mechanisms. The proposed model consists of three main pillars: regulatory reconstruction through the introduction of a *lex specialis* addressing violence against election officials; institutionalization of preventive and repressive protection measures, including hotlines and advocacy units; and optimization of institutional synergy, particularly through strengthening the role of the Gakkumdu Center and enhancing support from local governments.